Sterically stabilized end-on superoxocopper(II) complexes and mechanistic insights into their reactivity with O−H, N−H, and C−H substrates - Quek, Sebastian Y. (2022)
Instability of end-on superoxocopper(II) complexes, with respect to conversion to peroxo-bridged dicopper(II) complexes, has largely constrained their study to very low temperatures. This limits their kinetic capacity to oxidize substrates. In response, we have developed a series of bulky ligands, Ar3-TMPA (Ar = tpb, dpb, dtbpb), and used them to support copper(I) complexes that react with O2 to yield [CuII(η1-O2•-)(Ar3-TMPA)]+ species, which are stable against dimerization at all temperatures. Binding of O2 saturates at subambient temperatures and can be reversed by warming. The onset of oxygenation for the Ar = tpb and dpb systems is observed at 25 °C, and all three [CuII(η1-O2•-)(Ar3-TMPA)]+ complexes are stable against self-decay at temperatures of ≤-20 °C. This provides a wide temperature window for study of these complexes, which was exploited by performing extensive reaction kinetics measurements for [CuII(η1-O2•-)(tpb3-TMPA)]+ using a broad range of O-H, N-H, and C-H bond substrates. This includes correlation of second order rate constants (k2) versus oxidation potentials (Eox) for a range of phenols, construction of Eyring plots, and temperature-dependent kinetic isotope effect (KIE) measurements. The data obtained indicate that reaction with all substrates proceeds via H atom transfer (HAT), reaction with the phenols proceeds with significant charge transfer, and full tunneling of both H and D atoms occurs in the case of 1,2-diphenylhydrazine and 4-methoxy-2,6-di-tert-butylphenol. Oxidation of C-H bonds proved to be kinetically challenging, and whereas [CuII(η1-O2•-)(tpb3-TMPA)]+ can oxidize moderately strong O-H and N-H bonds, it is only able to oxidize very weak C-H bonds.